Role of CD86 in Detection of Minimal Residual Disease in Pediatric B-cell Acute Lymphoblastic Leukemia: A Prospective Study of 40 Pediatric Patients - Choudhary, Dr. Riva; Singh, Dr. Smita; Saxena, Dr. Rushali; Shukla, Dr. Shailaja; Mahto, Dr. Deonath (International Journal of Innovative Research in Medical Science, 2025)
Objective: This study aims to evaluate to utility of CD86 in minimal residual disease (MRD) detection in paediatric B-cell Acute Lymphoblastic Leukemia (ALL) for better patient management. Materials and Methods: Clinical data and flowcytometric analysis of B-cell ALL on day 0 and day 35 for MRD was collected prospectively from paediatric haematology oncology centres in India. Results: 40 children newly diagnosed with B-cell ALL between for MRD detection were enrolled in the study. Frequency of CD73, CD86 and CD123 were 90%, 70% and 60% respectively in diagnostic sample. In MRD positive samples, maximum frequency of CD86 (85.7%) and CD73 (85.7%) were observed followed by CD123 (71.4%). CD86 showed highest post-induction stability among all Leukaemia Associated Immunophenotype (LAIP) markers on blasts. Conclusion: CD86 has a significant expression in B-cell ALL in MRD detection with excellent post induction stability. Thus, inclusion of CD86 improves the utility of flowcytometry based routine clinical practice of MRD detection.